Occupational Hazards and its Impact on Health of Eyes: A Survey - Deshpande, Neeta A; Deshmukh, Pramod B; Thakare, Prateek (International Journal of Computer Sciences and Engineering, 2018)
This research has been undertaken to examine the impact of occupational hazards on health of Computer Professionals, The essential data have been collected using Community-Survey method. Additionally books, journals, and websites have been referred for getting certain conclusions from the collected survey samples. In this survey based descriptive research, Opinions of diverse Computer professionals in pune city, Maharashtra are taken to find out the average health of the eyes. This research also tries to find certain patterns on the usage of electronic gadget in a particular age group and their tendency towards getting a particular eye disease.